Defending the Status Quo in The Dark Knight Rises - Jesse Russell (European Journal of American Studies)
Although not as popular or groundbreaking as his Dark Knight, Christopher Nolan’s 2012 The Dark Knight Rises is an important cultural artefact of the twenty-first century. The film presents a number of villains who challenge the corrupt social order of Gotham City, which itself stands as a figure for twenty-first century American capitalism. Nonetheless, despite these criticisms, the film upholds American neoliberalism as the best of many flawed systems.